Evolution and Creationism in America's Classrooms: A National Portrait - Berkman, Michael B; Pacheco, Julianna Sandell; Plutzer, Eric (PLOS Biology, 2008)
Despite many legal and legislative decisions, a new study shows that one in eight high school biology instructors teach their students that creationism or intelligent design is a valid alternative to evolutionary biology.